Guns for Hire: The Privatization of Modern Wars - Marsili, M. (Rivista di Studi Politici Internazionali, 2024)
Modern warfare no longer requires large armies filled almost entirely by conscripts but professional, volunteer, and skilled soldiers. Commercialisation of force is evident in public use of private military contractors–just another wording for mercenaries. These trend opens new spaces for (semi)covered armed interventions and holds political and military leaders not accountable for crimes committed by hired guns. This paper explores the use of paramilitary in the context of contemporary conflicts and analyses the implications in the light of international (humanitarian) law.